2013
DOI: 10.1002/ab.21505
|View full text |Cite
|
Sign up to set email alerts
|

Relating sexual sadism and psychopathy to one another, non‐sexual violence, and sexual crime behaviors

Abstract: Sexual sadism and psychopathy have been theoretically, clinically, and empirically linked to violence. Although both constructs are linked to predatory violence, few studies have sought to explore the covariation of the two constructs, and even fewer have sought to conceptualize the similarities of violence prediction in each. The current study considered all four Psychopathy Checklist-Revised (PCL-R) facets and employed well-defined, validated measures of sadism to elucidate the relation between sadism and ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 79 publications
3
45
2
Order By: Relevance
“…Moreover, this process would give rise to individuals prone to deriving intrinsic pleasure from inflicting violence (i.e., sadism). Indeed, studies have identified an association between psychopathy and sadistic traits in adolescents (Decety et al, 2009), college students (Buckels, Jones, & Paulhus, 2013), and adult murderers (Porter et al, 2003; Robertson & Knight, 2014). …”
Section: Neuro-developmental Processesmentioning
confidence: 99%
“…Moreover, this process would give rise to individuals prone to deriving intrinsic pleasure from inflicting violence (i.e., sadism). Indeed, studies have identified an association between psychopathy and sadistic traits in adolescents (Decety et al, 2009), college students (Buckels, Jones, & Paulhus, 2013), and adult murderers (Porter et al, 2003; Robertson & Knight, 2014). …”
Section: Neuro-developmental Processesmentioning
confidence: 99%
“…Two dominant positions have been identified in the forensic literature concerning the personality profile of sexual offenders. In one viewpoint, Proulx and associates portray them as having schizoid and avoidant personalities (Knight & Prentky, 1990;Robertson & Knight, 2014). In another viewpoint, Knight and colleagues depict them as psychopathic and narcissistic (Beauregard et al, 2007;Proulx et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the correlation of sadism and Psychopathy Checklist scores revealed that sadism and psychopathy are covariate, but are not coextensive [23]. Sexual sadism and antisocial personality disorder are common among sexual homicide offenders.…”
Section: Sexual Sadism and Sexual Masochismmentioning
confidence: 98%
“…Robertson and Knight [23] conducted an empirical analysis of criminal behaviours showing that sadism and psychopathy consistently predicted sexual and nonsexual violence. An analysis of the correlation of sadism and Psychopathy Checklist scores revealed that sadism and psychopathy are covariate, but are not coextensive [23].…”
Section: Sexual Sadism and Sexual Masochismmentioning
confidence: 99%